Glycerol as a cheaper carbon source in bacterial cellulose (BC) production by Gluconacetobacter xylinus DSM46604 in batch fermentation system - Roslan, Umar; Azila, Adnan; Giridhar R., Nair (Malaysian Society of Analytical Sciences, 2015)
Bacterial cellulose (BC) is a polymer of glucose monomers, which has unique properties including high crystallinity and high strength. It has potential to be used in biomedical applications such as making artificial blood vessel, wound dressings, and in the paper making industry. Extensive study on BC aimed to improve BC production such as by using glycerol as a cheaper carbon source. BC was produced in shake flask culture using five different concentrations of glycerol (10, 20, 30, 40 and 50 g/L). Using concentration of glycerol above 20 g/L inhibited culture growth and BC production. Further experiments were performed in batch culture (3-L bioreactor) using 20 g/L glycerol. It produced yield and productivity of 0.15 g/g and 0.29 g/L/day BC, respectively. This is compared with the control medium, 50 g/L glucose, which only gave yield and productivity of 0.05 g/g and 0.23 g/L/day, respectively. Twenty g/L of glycerol enhanced BC production by Gluconacetobacter xylinus DSM46604 in batch fermentation system.